Clinical Application of Shear Wave Elastography for Assisting Brain Tumor Resection - Chan, Huan Wee; Uff, Christopher; Chakraborty, Aabir; Dorward, Neil; Bamber, Jeffrey Colin (Frontiers in Oncology, 2021)
Background: The clinical outcomes for brain tumour resection have been shown to be significantly improved with increased extent of resection. To achieve this, neurosurgeons employ different intra-operative tools to improve the extent of resection of brain tumours, including ultrasound, CT and MRI. Young’s modulus (YM) of brain tumours have been shown to be different from normal brain but the accuracy of SWE in assisting brain tumour resection has not been reported. Aims: To determine the accuracy of SWE in detecting brain tumour residual using post-operative MRI scan as ‘gold standard’. Methods: Thirty four patients (aged 1-62 years, M:F = 15:20) with brain tumours were recruited into the study. The intraoperative SWE scans were performed using Aixplorer (SuperSonic Imagine, France) using a sector transducer (SE12-3) and a linear transducer (SL15-4) with a bandwidth of 3-12 MHz and 4-15 MHz, respectively, using the SWE mode. The scans were performed prior, during and after brain tumour resection. The presence of residual tumour was determined by the surgeon, ultrasound (US) B-mode and SWE. This was compared with the presence of residual tumour on post-operative MRI scan. Results: The YM of the brain tumours correlated significantly with surgeons’ findings (p=0.845, p<0.001). The sensitivities of residual tumour detection by the surgeon, US B-mode and SWE were 36%, 73% and 94%, respectively, while their specificities were 100%, 63% and 77%, respectively. There was no significant difference between detection of residual tumour by SWE, US B-mode and MRI. SWE and MRI were significantly better than the surgeon’s detection of residual tumour (p=0.001 and p<0.001, respectively). Conclusions: SWE had a higher sensitivity in detecting residual tumour than the surgeons (94% vs 36%). However, the surgeons had a higher specificity than SWE (100% vs 77%). Therefore, using SWE in combination with surgeon’s opinion may optimise the detection of residual tumour, and hence improve the extent of brain tumour resection.